Socioeconomic characteristics of urban and peri-urban dairy production systems in the North western Ethiopian highlands - Ayenew, Y.A.; Wurzinger, Maria; Tegegne, Azage; Zollitsch, W. (Springer, 2011)
In order to evaluate the socio-economic characteristics of urban and peri-urban dairy production systems in the North western Ethiopian highlands, a field survey was conducted which included 256 farms. It is concluded that urban farmers tend to specialize on dairy production and support the family income from non-agricultural activities, while agricultural activities other than milk production forms an additional source of income in peri-urban farms. The specialization of urban dairy producers includes the more frequent use of crossbred cows with higher milk yield. Urban and peri-urban dairy production contributes to food security of the population and family income of the farmers' families, but also provides a job opportunity for otherwise unemployed people. Access to farm land, level of education and access to certain input services such as training, veterinary and credit services were identified as the major constraints for the future development of the dairy sector.